Politics after neoliberalism : reregulation in Mexico - Snyder, Richard (Richard Owen), 1967- (Cambridge studies in comparative politics., 2001)
The shift from state-led to market-oriented, neoliberal economic policies has been one of the most important changes in the developing world during the last two decades. Although much existing research has focused on why countries choose these neoliberal policy reforms and how they implement them, Richard Snyder's study offers an analysis of politics after neoliberalism. The book proposes a framework that explains how neoliberal reforms, rather than unleashing market forces, actually trigger 're-regulation' processes involving strategic interactions between political entrepreneurs and societal groups. Depending on the strengths and strategies of politicians and societal groups, reregulation results in different types of new institutions for market governance with contrasting consequences for economic efficiency and social justice. This framework is used in conjunction with an innovative subnational comparative method to analyze evidence from four Mexican states about the politics of reregulation.